Promoting Peacebuilding through Humanistic Learning in History Class - Ba'in, Ba'in; Suyahmo, Suyahmo; Pramono, Suwito Eko; Atmaja, Hamdan Tri; Shokheh, Muhammad; Hartatik, Endah Sri (History Department, Semarang State University and Historian Society of Indonesia, 2024)
This study aims to construct a history-learning scheme using a humanistic approach to create peace in the Boyolali region. This study used a descriptive method within the Cresswell framework. This study’s data sources were informants, consisting of fifteen participants. Data analysis applies an interactive model. The results showed that mass trauma related to past events, namely the 1965 Incident, still occurred in Boyolali, which is an indication of the ambivalence of society and has an impact on a less harmonious social situation. Reconciliation through education is necessary for creating a peaceful atmosphere. A history-learning scheme with a humanistic approach, which is constructed based on the phenomena and social conditions of the community, has succeeded in creating a proactive learning atmosphere to break hatred and spread the spirit of peace. In conclusion, history learning with a humanistic approach is relevant for creating a peaceful society, free of conflict and ambivalence, and able to think constructively about social development in the Boyolali region.Penelitian ini bertujuan untuk menyusun skema pembelajaran sejarah dengan pendekatan humanistik untuk menciptakan perdamaian di wilayah Boyolali. Penelitian ini menggunakan metode deskriptif dalam kerangka Cresswell. Sumber data penelitian ini adalah informan yang terdiri dari lima belas partisipan. Analisis data menggunakan model interaktif. Hasil penelitian menunjukkan bahwa trauma massal terkait peristiwa masa lalu yaitu Peristiwa 1965 masih terjadi di Boyolali yang merupakan indikasi ambivalensi masyarakat dan berdampak pada kurang harmonisnya situasi sosial. Rekonsiliasi melalui pendidikan diperlukan untuk menciptakan suasana damai. Skema pembelajaran sejarah dengan pendekatan humanistik yang dibangun berdasarkan fenomena dan kondisi sosial masyarakat berhasil menciptakan suasana pembelajaran yang proaktif untuk mematahkan kebencian dan menyebarkan semangat perdamaian. Kesimpulannya, pembelajaran sejarah dengan pendekatan humanistik relevan untuk mewujudkan masyarakat damai, bebas konflik dan ambivalensi, serta mampu berpikir konstruktif terhadap pembangunan sosial di wilayah Boyolali.